If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1 + 3(4 + -4x) = 0 9x + -1 + (4 * 3 + -4x * 3) = 0 9x + -1 + (12 + -12x) = 0 Reorder the terms: -1 + 12 + 9x + -12x = 0 Combine like terms: -1 + 12 = 11 11 + 9x + -12x = 0 Combine like terms: 9x + -12x = -3x 11 + -3x = 0 Solving 11 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -3x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -3x = 0 + -11 -3x = 0 + -11 Combine like terms: 0 + -11 = -11 -3x = -11 Divide each side by '-3'. x = 3.666666667 Simplifying x = 3.666666667
| 7x+2x=8x-1 | | -5.2M+11015=-3041 | | 3x+16=4x+13 | | 4t-t-7=2t-8 | | 15x+40=-88 | | 6x+x-8=6x+4 | | .56-0.32=1.12 | | 4x+32=8x+4 | | 4.3y=-3.44 | | 4/9=h/24 | | 2x+4x=26 | | 1/6X-17.1=-18 | | 4x+9x-63=84-8x | | 4(8-c)=8c+16-6c | | 28=(x-.5)+9 | | 28x+12y=8 | | 8y/6+3/6=5y/6 | | -39+8m=-5(1-5m) | | 10-9v+v= | | 5+3(2x-4)=9-4+(3x+1) | | 6*26= | | 3n+n=236 | | 5x+7x-38=95-7x | | x^2+3x+14=24 | | (3x^2)+2x-15=0 | | -7y+2=5y-7 | | y^2-3=y+9 | | 2(4x-4)+2(3x-2)=360 | | 21x^2-18x^3=6x | | -56=-49t | | 7x-4y=-26 | | 7x-2(4-3x)=3(2x+1) |